Intramuscular mRNA BNT162b2 vaccine against SARS-CoV-2 induces neutralizing salivary IgA - Miri Stolovich-Rain; Miri Stolovich-Rain; Miri Stolovich-Rain; Sujata Kumari; Sujata Kumari; Sujata Kumari; Ahuva Friedman; Ahuva Friedman; Saveliy Kirillov; Saveliy Kirillov; Saveliy Kirillov; Saveliy Kirillov; et al. (Frontiers in Immunology, 2023)
Intramuscularly administered vaccines stimulate robust serum neutralizing antibodies, yet they are often less competent in eliciting sustainable “sterilizing immunity” at the mucosal level. Our study uncovers a strong temporary neutralizing mucosal component of immunity, emanating from intramuscular administration of an mRNA vaccine. We show that saliva of BNT162b2 vaccinees contains temporary IgA targeting the receptor-binding domain (RBD) of severe acute respiratory syndrome coronavirus-2 spike protein and demonstrate that these IgAs mediate neutralization. RBD-targeting IgAs were found to associate with the secretory component, indicating their bona fide transcytotic origin and their polymeric multivalent nature. The mechanistic understanding of the high neutralizing activity provided by mucosal IgA, acting at the first line of defense, will advance vaccination design and surveillance principles and may point to novel treatment approaches and new routes of vaccine administration and boosting.